(3GdBKGQ GdfGTFI Yf OeL GdTQcGJ GdeSGgeI (B/s - (3Gdajhej, djfG jYbhHs ((3HjQhJ(B: s (3efThQGJ GdMdHj(B, s, 2009)
1)(3BKGQ GdOeL Ydi GdGehGd (B: (3eaghe GdPeI GdeGdjI heUjQgG YfO GdOeL , eUjQ GdYbhO GdeHQeI ef GdTQcGJ GdeSGgeI YfO GdOeL , YbO GdGjLGQ h YbO GdYed (B2) (3BKGQ GdOeL Ydi GdGTNGU (B: (3GdOeL HGdfSHI ddCYVGA aj GdTQcI , GdOeL HGdfSHI ddZjQs
(3eQGLY U(B.153s
Keywords: (3GdTQcGJs; (3GdTQcGJ GdeSGgeI GdeMOhOIs